Innovation processes in science and education - Гладкіх, Тамара; Онуфрієнко, Олексій; Чувакова, Тетяна; Правова, Нінель; Маркелов, Андрій; Кондратенко, Юлія; Котлова, Людмила; Долінчук, Ірина; Шеховцева, Ольга; Онуфрієнко, Володимир; Засовенко, Андрій; Ткаченко, Андрій; et al. (DEL a.s., 2022)
The collection includes materials of the IV International Research and Practical Internet Conference "Innovation processes in science and education". The materials of the collection will be useful for researchers, scientists, graduate students, researchers, teachers, students